Single-phase shunt active power filter based on a 5-level converter topology - Pinto, J. G. (2018)
José Gabriel Oliveira Pinto is the mentor of the idea of using the 5-level asymmetric full-bridge topology as a single-phase shunt active filter, participated in the development of the experimental prototype by designing some of the PCBs, and coordinated the organization and writing of the paper. Rui Macedo is the responsible for the implementation of the simulation model, hardware prototype, obtainment of the simulation results and experimental results, and participated in the writing of the paper. Vitor Monteiro participated in the design of the hardware prototype, sizing of electronic components, design of the predictive current control and writing of the paper. Luis Barros participated in the development of the hardware prototype, obtainment of the experimental results and writing of the paper. Tiago Sousa participated in the hardware prototype development, design of the SPWM modulation technique and writing of the paper. João L. Afonso participated in the design of the control algorithms based on the p-q theory, in the adaptation of the p-q theory to single-phase systems and in the writing of the paper.